Biofilms in Food Processing: A Comprehensive Review of Understanding Formation, Challenges, and Future Directions - Ligi Lambert D Rosario; Harsha Mohan; Febiya Anna Fedin; Sona S Dev (The Bioscan, 2024)
Biofilms are complex communities of microorganisms attached to the surfaces and can cause cross-contamination of foods. Biofilms are irreversibly linked with a surface inside an extracellular polymeric substance matrix (EPS) which is challenging for the food industry. There exists an urgent need for disinfectants or new technologies to restrict reversible and irreversible attachment which are the main cause of surface tension of microorganisms that leads to surface adhesion. Many articles have reported the negative effects of biofilm production in the food industry and the role of microorganisms such as Bacillus cereus, and Listeria monocytogenes in foodborne diseases. This review paper discusses the formation and characteristics of Biofilm, the structure and composition of biofilms, factors influencing biofilm development, the presence of biofilms in food processing environments, the type of microorganisms present in the biofilms, and strategies and controlling measures for preventing biofilm formation. The article also discussed some positive impacts of biofilms in various applications.